Biodegradation and Microbial Contamination of Limestone Surfaces: An Experimental Study from Batalha Monastery, Portugal - Schiavon, Nicola (2022)
An experimental study was conducted to assess the nature and extent of the biodeterioration of the limestone in the Batalha Monastery in Portugal. Stone fragments covered with microbial biofilms and lichenous crusts were investigated using Optical Microscopy (OM), Low Vacuum Scanning Electron Microscopy with Energy Dispersive Spectroscopy (LV-SEM + EDS), and X-ray micro-Diffractometry ( -XRD). Microbial samples were collected from the stone surface, cultured, and analyzed with NGS metagenomic DNA test to classify the bacterial communities associated with the formation of the biofilms. Particulate air pollutants collected on Pall GN-6 paper filters using a cascade impactor were characterized by SEM-EDS + NGS. The results showed that lichens play a major role in biodeterioration by promoting both physical and chemical attack on the limestone substrate via hyphae mechanical penetration along calcite inter-crystalline spaces, the dissolution/leaching of calcite minerals, and the precipitation of secondary minerals such as Ca-oxalates within the stone porosity framework. DNA analyses identified the bacterial communities within the biofilms and their relative abundances. Air quality monitoring results suggest that the microbial population colonizing the monastery limestone could at least partially be derived from the dry and wet deposition of airborne biological particles on the stone surfaces and that S, N, and P-rich air pollutants may have provided nutrients and energy for the bacteria communities, thus indirectly facilitating biofilm formation, the growth of a lichenous crusts, and limestone biodeterioration effects.